Handbook of guidance services - Gazda , George M.; Folds, Jonell H. (Urbana, Illinois : R.W. Parkinson, 1966)
This book represents an attempt to provide the practicing counselor with a compendium of approaches for implementing the guidance services. To be sure, most of the activities are not our ideas, but rather come from a variety of sources - each one carefully documented. It was because of the paucity of "how to" suggestions in any single source that the present volume was written.
1. Introduction -- 2.Orientation -- 3. Testing -- 4. Counseling -- 5. Placement -- 6. Follow-up.
Includes bibliographical references.
Keywords: COUNSELING